2004
DOI: 10.1016/j.ymthe.2004.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and transcription factor gene therapy in experimental parkinson's disease: sonic hedgehog and gli-1, but not Nurr-1, protect nigrostriatal cell bodies from 6-OHDA-induced neurodegeneration

Abstract: We tested the activity of the dopaminergic neuron differentiation factor sonic hedgehog, its downstream transcription factor target Gli-1, and an orphan nuclear receptor, Nurr-1, necessary for the induction of the dopaminergic phenotype of nigrostriatal neurons, in an in vivo model of nigrostriatal neurodegeneration. Our preliminary experiments demonstrated that all three constructs expressed the proper molecules and that these had the predicted biological activities in vitro. We expressed the N-terminal of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 80 publications
5
37
0
Order By: Relevance
“…Also, the immunostaining for TH-immunoreactive fibers in the striatum indicated that, as had been described by us recently, 33,34 only GDNF (Figure 6b) was able to partially preserve striatal dopaminergic fibers ( Figure 6). Only in animals injected intrastriatally with RAd-GDNF did we detect a halo of intense THimmunoreactive fibers surrounding the intrastriatal injection site (Figures 6b and 7).…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…Also, the immunostaining for TH-immunoreactive fibers in the striatum indicated that, as had been described by us recently, 33,34 only GDNF (Figure 6b) was able to partially preserve striatal dopaminergic fibers ( Figure 6). Only in animals injected intrastriatally with RAd-GDNF did we detect a halo of intense THimmunoreactive fibers surrounding the intrastriatal injection site (Figures 6b and 7).…”
Section: Resultssupporting
confidence: 80%
“…The vectors RAd-GDNF and RAd-hCMV-Gli1 have been described by us recently, 33,34 as has the vector expressing the control marker transgene b-galactosidase under the control of the hCMV promoter. [41][42][43][44] The neuroprotective paradigm used was adapted to our particular needs from the detailed 6-OHDA rat model of Parkinson's disease 2,3 In our experiments, the RAds were injected stereotaxically into the rat striatum using the same coordinates as used for the retrograde tracer fluorogold (FG) (Figure 4, and described in detail in Hurtado-Lorenzo et al 33,34 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations